Changes in the Water Footprint during COVID-19 at Santa Rosa Hospital Located In Metropolitan Lima City, Peru - Cáceres, Wilfredo Salas (2024)
This study aims to investigate the water footprint of Santa Rosa Hospital, situated in the city of Lima, Peru. The analysis period covers the years 2015 to 2019, before the onset of the COVID-19 pandemic, and the period from 2020 to 2022, after the COVID-19 pandemic. The primary objective is to understand how the health crisis has impacted water consumption and to identify measures taken to optimize its usage. The methodology involves the calculation of both blue and grey water footprints, with the green footprint excluded due to the absence of green areas in the hospital premises. Data essential for determining the water footprint were sourced from technical reports published by public scientific entities. The findings revealed an increase in the water footprint following the onset of COVID-19. A management study implemented significant savings for the year 2022. Through this analysis, the hospital aims to reinforce its commitment to sustainable water management, contributing to a healthier and more environmentally sustainable future.